1988
DOI: 10.1002/jso.2930370303
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to the aids virus in Kaposi's sarcoma in Nigeria

Abstract: The present study has investigated whether Kaposi's sarcoma (KS) in Nigeria is associated with infection with the AIDS virus variously called human T-cell lymphotropic virus type III (HTLV-III), lymphadenopathy/AIDS virus (LAV), and AIDS-associated retrovirus (ARV). Serum samples from 40 KS patients, 30 patients with malignant melanoma of the foot (contemporaneous controls), and 50 normal nontumour-bearing controls were tested for anti-AIDS virus antibody by enzyme-linked immunosorbent assay (ELISA). The assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Endemic African KS has accounted for 10% of cancers and has been observed in a male‐to‐female ratio of 15 : 1 16 . This disease is highly endemic in equatorial African countries such as the Congo Republic, Uganda, and Zambia 17 . The Kampala Cancer Registry has shown a significant change in the incidence of KS in the era of AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Endemic African KS has accounted for 10% of cancers and has been observed in a male‐to‐female ratio of 15 : 1 16 . This disease is highly endemic in equatorial African countries such as the Congo Republic, Uganda, and Zambia 17 . The Kampala Cancer Registry has shown a significant change in the incidence of KS in the era of AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Akinsete et al 31 found a prevalence of 0.52% in a study in Lagos in 1996, whereas Onyemelukwe and Musa 32 reported a prevalence of 2% in a 1997 study in Zaria. Compared with prevalence in the United States, where rates ranging from 15% to 40% have been recorded at different times in the pandemic, [1][2][3]17,33,34 it could be said that the prevalence in Nigeria is low but appears to be rising. With the increasing availability and accessibility of antiretroviral medications in the country through the efforts of the Federal government supported by the US government, it is expected that the incidence of AAKS will decrease with a resultant decrease in the prevalence, at least in the short and medium term.…”
Section: Discussionmentioning
confidence: 99%
“…The ages and the CD4 count at onset of the disease found in the study were in line with previous findings. 1,3,7,32,34,35 However, it would appear that women present at relatively earlier ages and lower CD4 counts than do men. Although the reason for this finding is not clear, it may be that women acquired the associated/etiologic virus HHV-8 21 as well as HIV at earlier ages because it is known that women tend to begin sexual intercourse earlier than do men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations